Educational Blog: Teacher Assistance In Creating Learning Media - Wijaya, Guruh; Sulistyo, Henny Wahyu; Arifin, Zainul (Journal Of Humanities Community Empowerment, 2023)
The development of information and communication technology through the Internet has a significant impact on people's lifestyles, including the practice of blogging as an expression of Internet use. Blogging has penetrated into various aspects of life, one of which is in the context of education. In the world of education, blogs have a very important role as a tool to store and disseminate information online. Its use can be personal, such as for teachers who want to share teaching materials, learning reflections, or personal experiences in the teaching process. On the other hand, educational institutions also utilize it as a platform to provide information to students, parents, and the general public. The main advantage of blogs in education is their ability to present information easily and quickly, without being bound by space and time constraints. In essence, blogs open up wide access to knowledge. The purpose of this activity is to introduce students to basic knowledge and skills in creating blogs that support interaction, in accordance with their respective fields of knowledge. One-day blogging training has proven to be quite effective for teaching the technical details of creating a blog as well as how to load material to be interactive and engaging. More than just technical training, it is the first step towards achieving a larger goal in education. A total of 14 participants from teachers and learning staff of SMPN 2 Jember have taken blogging insight tests before and after the training to support their learning process. The test results showed that before the training, knowledge about blogging was still lacking. However, after the training, participants were able to significantly improve their comprehension, as seen from the increase in the number of questions that can be answered and the higher level of accuracy in the post-test session. Thus, future follow-up activities related to the introduction of blogging for teachers and staff will focus on increasing understanding and knowledge of the role of blogging in creating dynamic learning materials for the improvement of education quality